Má absorção das hormonas tiroideias. - E Lacerda Nobre; Zulmira Jorge; J Anselmo; Carlos Lopes; Rui César; V Santos; J Jácome de Castro (Acta Médica Portuguesa, 2004)
We describe the case of a 22-year old male undergoing a total thyroidectomy for euthyroid multi-nodular goitre (TSH: 1.6 microUI/ml). He was discharged treated with LT4 100 mg id. After discharge, he went into full clinical and laboratorial hypothyroidism (TSH = 396 microUI/mL). We were able to rule out failure to take the medication and concomitant use of drugs. In the evaluation of intestinal absorption, only the D-Xylose test proved to be abnormal. After unsuccessful administration of oral T4 and T3, under close nursing supervision, intramuscular (IM) and subcutaneous (SC) forms of administration of T4 were experimented. While both forms achieved normal levels of thyroid hormones, we opted for IM injection as the patient complained of local pain during SC administration. This seems to be the second case described in which it was necessary to resort to parenteral administration of T4 to achieve clinical and laboratorial euthyroidism.